Validation of an evaluation matrix for the nursing process in the hospital context - Jocelio Matos Amaral; Deybson Borba de Almeida; Genival Fernandes de Freitas; João Paulo de Almeida Tavares (Universidade Federal do Rio Grande do Sul, 2024)
ABSTRACT Objective: To validate the content of an evaluation matrix for the nursing process in the hospital context. Method: A methodological study conducted in four stages, carried out from March to December 2022. Including: bibliographic research and selection of structuring foundations; construction of the logical model and analysis and judgment matrix; content validation by a committee of judges (n=11) using the Delphi technique; analysis of content validation data by calculating the Concordance Rate and Content Validity Index. Results: At the end of the two rounds, the matrix had a concordance rate of 90% regarding format and 100% regarding other structural aspects. It also had a 100% concordance rate regarding the scope and representativeness of the matrix domains. Regarding the average Content Validity Index, the values were 0.97 and 0.98, for clarity and representativeness, respectively. Conclusion: The evaluation matrix - consisting of four dimensions and fourteen evaluation items referring to the necessary stages for the implementation and operationalization of the nursing process - demonstrated excellent content validity, which can contribute to supporting institutional initiatives for its consolidation in hospital nursing services.